Making an Old-world Milwaukee: German Heritage, Nostalgia, and the Reshaping of the Twentieth Century City - (:unkn) unknown (My University, 2017)
This dissertation examines the importance of white ethnicity, and especially Germanness, in the “civic branding” and urban restructuring efforts of city officials, civic boosters, and business leaders in Milwaukee, Wisconsin in the mid-to-late twentieth century. Scholars have increasingly identified the significant roles the “revival” of European ethnic identities played in maintaining white racial privilege in response to the Civil Rights Movement since the 1960s. I contribute to these new veins of scholarship by tracing the continued and evolving prominence of Germanness in the Midwestern city of Milwaukee, long after common assumptions of ethnic assimilation might have expected such nineteenth century German ethnic identities to have “melted” into American society. My research in civic and community organization records, as well as local newspaper stories, reveals the active, yet often-uncoordinated efforts of various cultural agents and power brokers to maintain white ethnic, German hegemony in Milwaukee between the 1920s and 1980s. The combined crises of World War, National Prohibition, and a perceived weakening of German influence in the diversifying city prompted civic boosters and business interests who relied on the privileged place of Germanness in Milwaukee’s social order to secure German hegemony in nostalgic memories of “Old Milwaukee” in the 1920s through 1940s. These narratives offered carefully crafted visions of Milwaukee’s Germanness as productive, pragmatic, yet fun, and characterized German cultural contributions—especially the festivity and hospitality associated with gemütlichkeit—as essential to the city’s nineteenth century development and charming Old World character. As working class politics, growing racial inequality, and civil rights movements challenged Milwaukee’s prevailing social order in the decades following the Second World War, business leaders, developers, and pro-business public officials deployed these narratives of heritage and nostalgia in their efforts to reimagine the city as a post-industrial tourist and entertainment destination. In the process, such constructions effectively secured white ethnic claims to power and privilege in urban space. Repeatedly elided from visions of Old Milwaukee, people of color negotiated a progressively uneven socio-economic urban terrain in which they were considered perennial tenants. Meanwhile, these same visions encouraged white ethnic residents and visitors to think of the city as inherently “theirs.”
Keywords: Ethnicity; German-americans; Milwaukee; Nostalgia; Race; Urban Renewal